Evaluation the current specifications for bridge in mountainous area of Vietnam. (December 2020) - Nguyen, Xuan Tung; Hoang, Viet Hai
Abstract: Vietnam area is more than 320, 000 square kilometers and three – forth are mountainous area. The transportation in this mountainous is very hard. Due to the mountainous geography, there is a lack of bridge which allow pedestrian or low – loading vehicle passing through. Besides the technical specification that was officially issued only cover the bridge on Highway and rural road. In this paper, the results of survey of bridge condition at 3 mountainous provinces is introduced and the evaluation of current specification, the basic technical specifications for mountainous bridges are also proposed.